Design, When Everybody Designs: An Introduction to Design for Social Innovation - Manzini, Ezio; Coad, Rachel (Design thinking, design theory, 2015)
In a changing world everyone designs: each individual person and each collective subject, from enterprises to institutions, from communities to cities and regions, must define and enhance alife project. Sometimes these projects generate unprecedented solutions; sometimes they converge on common goals and realize larger transformations. As Ezio Manzini describes in this book, we are witnessing a wave of social innovations as these changes unfold -- an expansive open co-design process in which new solutions are suggested and new meanings are created. Manzini distinguishes betweendiffuse design(performed by everybody) andexpert design(performed by those who have been trained as designers) and describes how they interact. He maps what design experts can do to trigger and support meaningful social changes, focusing on emerging forms of collaboration. These range from community-supported agriculture in China to digital platforms for medical care in Canada; from interactive storytelling in India to collaborative housing in Milan. These cases illustrate how expert designers can support these collaborations -- making their existence more probable, their practice easier, their diffusion and their convergence in larger projects more effective. Manzini draws the first comprehensive picture of design for social innovation: the most dynamic field of action for both expert and nonexpert designers in the coming decades.